Predictor Accuracy of Absolute Neutrophil Count in Early Onset Sepsis - Panchal, Nirav S; Chavda, Bipin H (Annals of Pathology and Laboratory Medicine, 2018)
Background: The most important causes of mortality in infants are sepsis, prematurity, low birth weight, birth trauma and neonatal asphyxia. Absolute neutrophil count is faster, easier, cheaper and simpler laboratory parameter to be used for prediction of early onset sepsis. This study is aimed to measure the influence of change in the absolute neutrophil count on babies born to mothers having risk factors for infection. Methods: Design of the study was cohort prospective model. Total 123 patients were included in the study after considering appropriate inclusion criteria. The patients were divided into 3groups: ANC (Absolute neutrophil count) < 1800/cmm, ANC 1800-5399/cmm and ANC > 5400/cmm. Results were analysed by GraphpadInstat Demo. Results: New born to mothers having risk factors for sepsis with high ANC (>5400/cmm) and normal ANC (1800-5399/cmm) shows a significant difference with p=0.000 (p<0.05); Odds ratio 9.35, sensitivity 82.8%, specificity 65.9%, positive predictive value79.4% and negative predictive value 70.7%. Conclusion: Incidence of early onset sepsis is 9.35 times higher in new borns born to mothers with risk factors for sepsis having higher ANC (particularly >10000/cmm) than those having ANC level within normal limits.